Implementasi Kebijakan Eliminasi Malaria di Kabupaten Sintang (Studi di Desa Emparu Baru Kecamatan Dedai) - Sandur Aprisca Sihol Bunga; Erdi Erdi; Siti Aisyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the implementation of the malaria elimination policy in Sintang Regency, specifically in Emparu Baru Village, Dedai District, and to identify factors influencing its success and obstacles. The research method used was a qualitative descriptive approach. Data were collected through in-depth interviews, observation, and documentation with parties directly involved in the malaria elimination program. Data were then analyzed using George C. Edward III's policy implementation theoretical framework, which encompasses aspects of communication, resources, disposition, and bureaucratic structure. The results indicate that policy communication has been implemented through face-to-face socialization, the provision of information media, and guidebooks. However, the role of the Village Malaria Post (Posmaldes) has not been optimal due to limited assistance and operational costs. In terms of resources, the Emparu Community Health Center in Dedai District still lacks health workers with backgrounds in health promotion and environmental health, and there are limited supporting facilities such as the availability of medicines and diagnostic tools. Furthermore, despite support from stakeholders, the implementation of Clean and Healthy Living Behaviors (PHBS) in the community has not been optimal, potentially increasing the risk of malaria transmission. The conclusions of this study indicate that the implementation of the malaria elimination policy in Emparu Baru Village has not been optimal. Therefore, strengthening resources, increasing the role of the Village Health Post (Posmaldes), improving public health behaviors, and developing clear Standard Operating Procedures (SOPs) at the village level are needed to support the achievement of the malaria elimination target. Keywords: Policy Implementation, Malaria Elimination, Resources, PHBS